Modeling newsvendor behavior: A prospect theory approach - UPPARI, Bhavani Shanker (Institutional Knowledge at Singapore Management University, 2019)
Problem definition: Studies have shown that the behavior of subjects in newsvendor experiments is not consistent with expected profit maximization - an assumption that is often made in operations management literature. Although prospect theory has been established as a popular model of behavioral decision making under uncertainty, it was considered to be inconsistent with observed newsvendor behavior (in particular, the pull-to-center effect) until a recent study proposed a prospect theory model that is consistent with the pull-to-center effect; however, this model's ability in representing newsvendor behavior compared to other plausible prospect theory models is unexplored in the literature. This paper takes a more comprehensive approach in building several prospect theory-based newsvendor models, and evaluates their competence in representing the observed newsvendor behavior. An important feature of these models is that they are not only consistent with the pull-to-center effect, but they can also, in accordance with the findings from recent research, accommodate individual-level heterogeneity in order quantities.